The Quality of Counseling Center in Batanghari Regency, Jambi - Denmar, Denny; Ekawarn; Suratno; Saudagar, Ferdiaz; Muspawi, Mohamad; Rahmawati, Sophia (International Journal of Psychosocial Rehabilitation, 2020)
The purposes of this research are to look at the relationship between: 1) Management and quality of Counseling Center (Counseling centers), 2) Integrity of Head of Counseling Center and Counseling Center quality, 3) Environment and quality of Counseling Center, 4) Management, Integrity of Head and environment together with quality of Counseling Center in Batanghari Regency, Jambi The research was conducted in July 2019 involving 150 field extension workers (PPL) with a purposive sampling method and analyzed with correlation regression.The research results showed that there was a significant and linear relationship between: 1) Counseling Center management and Counseling Center quality with its regression equation Y = -5.83 + 0.92 X1, 2) Integrity of head of Counseling Center and Counseling Center quality with equation Y = 43.780 + 0.584 X2 , Counseling Center environment and Counseling Center quality with its regression equation Y = 13,010 + 0,950X3 4) Management, integrity of head and environment of Counseling Center with equation Y = -43,271 + 0,470 X1 + 0.290 X2 + 0,673 X3, coefficient of determination (R2) This research is 0.63 showing that 63% of the variation that occurs in quality is explained by Counseling Center management, integrity of head of Counseling Center, and Counseling Center Environment.